2014
DOI: 10.1186/0717-6287-47-24
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the phytochemical constituents and antioxidant activity of a bloom forming microalgae Euglena tuba

Abstract: BackgroundUnstable generation of free radicals in the body are responsible for many degenerative diseases. A bloom forming algae Euglena tuba growing abundantly in the aquatic habitats of Cachar district in the state of Assam in North-East India was analysed for its phytochemical contents, antioxidant activity as well as free radical scavenging potentials.ResultsBased on the ability of the extract in ABTS•+ radical cation inhibition and Fe3+ reducing power, the obtained results revealed the prominent antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 34 publications
(48 reference statements)
0
30
0
Order By: Relevance
“…In the industrial wastewater we used in this study the majority of nitrogen is in the form of ammonia. Among the above nitrogen forms, ammonium is the most preferred form of nitrogen source for some microalgae in part because its uptake and utilization by microalgae is most energy efficient [ 11 , 21 ]. It is commonly accepted that nitrogen metabolism is linked to carbon metabolism in algae because they share organic carbon and energy supplied directly from photosynthetic electron transport and CO2 fixation as well as from the metabolic pathway of organic carbon [ 23 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the industrial wastewater we used in this study the majority of nitrogen is in the form of ammonia. Among the above nitrogen forms, ammonium is the most preferred form of nitrogen source for some microalgae in part because its uptake and utilization by microalgae is most energy efficient [ 11 , 21 ]. It is commonly accepted that nitrogen metabolism is linked to carbon metabolism in algae because they share organic carbon and energy supplied directly from photosynthetic electron transport and CO2 fixation as well as from the metabolic pathway of organic carbon [ 23 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are only few published studies regarding the identification and quantification of phenolic composition in microalgae species [ 8 , 11 , 20 , 21 ]. Abd El-Baky et al .…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the power of a compound is the significant indicator of its antioxidant activity (Liu et al, 2013). It is related to their electron transfer ability and they can act as primary and secondary antioxidants (Chaudhuri et al, 2014). An increase in the absorbance at 700 nm indicates high reducing ability.…”
Section: Discussionmentioning
confidence: 99%
“…have a broad range of medicinal properties, such as antimicrobial, anti-mutagenic, anti-HIV, immunopotentiating and antitumor activity [ 15 20 ] with numerous isolated bioactive compounds such as, vitamin C, vitamin E and β-carotene that can be harnessed for commercial use [ 21 ]. In our previous study, we reported that E. tuba possess potent in vitro antioxidant and in vivo iron chelation activity [ 22 , 23 ] and numerous phytochemicals such as phenolics, flavonoids, alkaloids, tannins, terpenoids, triterpenoids, saponin, glycoside and carbohydrates are present in adequate amount in the extract which was confirmed by phytochemical analysis [ 22 ]. In this study, we first demonstrated the antiproliferative effect of 70 % methanolic extract of E. tuba (ETME) on lung and breast cancer cells and normal fibroblast cells in vitro.…”
Section: Introductionmentioning
confidence: 90%